Makna Term Malaikat Dalam Al-Quran Perspektif Semantik Toshihiko Izutsu - Chasanah, Chulsum Layyinatul; Pratama, Pradika Yoga; Lessy, Zulkipli (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Angels are supernatural creatures created by Allah with various tasks and characteristics given to them. Even though angels are invisible to human senses, the Qur'an proves that the existence and information of angels definitely exists.This research uses the key term angels in the Koran using semantic concepts. The data obtained was by collecting verses that contain the word angel. The primary source was obtained from Toshihiko's book